The Development of the Restaurant Business in Russia - KRYUKOVA, Elena; BODNEVA, Natalya; SRIBNAYA, Tatiana; FILIMONOVA, Nadezhda; VERSHININA, Olga (Journal of Environmental Management and Tourism, 2019)
The development of the restaurant business in Russia is a complex process, which combines advanced world technologies and established national traditions. Globalization has brought to the food service industry in Russia the service philosophy, the culture of service quality and competition at the level of national cuisines, as well as at the level of individual restaurants, including chain restaurants. During fledging years the restaurant business in the country contributed to the formation of a culture of visiting restaurants and other public eating places in different target audiences. In order to understand the essence of the restaurant business in Russia, it is necessary to consider the historical aspects of its development: the genesis of the service culture, the priority of national cuisines in restaurants, as well as the emergence and spread of enterprise types depending on time periods. Reviewing the history of restaurant business development, it is worth noting that this industry in Russia has undergone significant changes in the course of its evolution and formation. The conducted study of the noted problems will allow giving a holistic view of the restaurant business in the contemporary Russian economy.